Evaluating the combined use of ARVs and PrEP: Potential impact and challenges in high-risk populations - Mncedisi Willie, Michael (Journal of Chitwan Medical College, 2025)
Human immunodeficiency virus (HIV) remains a significant public health challenge globally. While antiretroviral therapy (ARVs) and pre-exposure prophylaxis (PrEP) are proven interventions for prevention and treatment, their integration is hindered by barriers such as poor adherence, stigma, economic constraints, and limited healthcare infrastructure. This study aimed to explore the challenges and opportunities associated with integrating ARVs and PrEP into HIV prevention strategies. This narrative literature review synthesised evidence from multiple peer-reviewed studies addressing adherence challenges, stigma, healthcare access, and the economic implications of ARVs and PrEP. Data sources included global and regional research focused on low and middle-income settings. Findings revealed that adherence remains a critical concern, influenced by side effects, pill burden, stigma, and psychosocial factors. Economic barriers and limited healthcare access reduce uptake, particularly in resource-limited contexts. Nevertheless, evidence suggests that integrating ARVs and PrEP could significantly reduce HIV transmission rates and healthcare costs. Public awareness and targeted education are essential in overcoming stigma and improving adherence. Strengthening the integration of ARVs and PrEP into HIV prevention requires community-based education, enhanced healthcare infrastructure, and innovative financing mechanisms. Policy interventions should prioritise stigma reduction and support for adherence. Future research should focus on long-term adherence strategies, cost-effective distribution models, and mitigating drug resistance to maximise the effectiveness of ARVs and PrEP in combating HIV/AIDS.